Models for Sustainable Framework in Luxury Fashion Luxury and Models (Textile Science and Clothing Technology,, 2018)
This book highlights the models developed to create a sustainable framework suitable for luxury in the textile sector and the innovative attempts in the luxury fashion and fabrics industry. The three chapters in this book discuss these issues by means of case studies and the future of such models.